Prevalensi Kristal Urat dalam Urin pada Subjek Dewasa Muda Berat Badan Lebih dan Obes - Tedjo, Tierza C. H.; Rambert, Glady I.; Monga, Arthur E. (Medical Scope Journal, 2020)
Abstract: Overweight and obese are conditions in which abnormal fat is accumulated in the body that may cause health problems. According to WHO, especially in the Asia-Pacific region, the BMI ≥23kg/m is considered overweight and ≥25kg/m is considered obese. This study was aimed to evaluate whether urate crystals were found in the urine of young adults with overweight and obese. This was an observational and descriptive study. Samples were chosen by using non-probability sampling with consecutive sampling type. The results showed that there were 60 young adults as subjects, consisting of 24 males (40%) dan 36 females (60%). There were 22 overweight subjects (36.7%), 24 obese-1 subjects (40%), and 14 obese-2 subjects (23.3%). Of 60 subjects, urine amorph crystals were found in 32 subjects (58.3%) meanwhile oxalate calcium crystals were found in 12 subjects (20%). In conclusion, among young adults with overweight and obese, the prevalence of urine amorph urate crystal was 58.3% and of urine oxalate calcium crystal was 20%.Keywords: overweight, obese, urine crystal, amorphous urate crystal, calcium oxalate crystal Abstrak: Berat badan lebih dan obes adalah keadaan akumulasi lemak abnormal atau berlebih yang dapat mengganggu kesehatan. Menurut WHO, khususnya untuk area Asia-Pasifik, seseorang dikatakan tergolong berat badan lebih jika IMT-nya ≥23kg/m2 dan obes jika ≥25kg/m. Penelitian ini bertujuan untuk mengevaluasi adanya kristal urat dalam urin dewasa muda dengan berat badan lebih dan obes. Jenis penelitian ialah deskriptif observasional. Sampel diperoleh dengan menggunakan non-probability sampling jenis consecutive sampling. Hasil penelitian menda-patkan sebanyak 60 dewasa muda yang memenuhi kriteria inklusi penelitian, terdiri dari 24 orang laki-laki (40%) dan 36 orang perempuan (60%). Di antaranya terdapat 22 orang (36,7%) berat badan lebih, 24 orang (40%) obes 1, dan 14 orang (23,3%) obes 2. Dari 60 subyek, ditemukan kristal urat amorf pada 32 orang (58,3%) dan kalsium oksalat pada 12 orang (20%). Simpulan penelitian ini ialah pada dewasa muda dengan berat badan lebih dan obes, prevalensi kristal urat amorf urin sebesar 58,3% dan kristal kalsium oksalat urin sebesar 20%.Kata kunci: berat badan lebih, obes, kristal urin